2024
DOI: 10.1007/s00330-024-10619-5
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-/perfusion-weighted imaging fusion to automatically identify stroke within 4.5 h

Liang Jiang,
Jiarui Sun,
Yajing Wang
et al.

Abstract: Objectives We aimed to develop machine learning (ML) models based on diffusion- and perfusion-weighted imaging fusion (DP fusion) for identifying stroke within 4.5 h, to compare them with DWI- and/or PWI-based ML models, and to construct an automatic segmentation-classification model and compare with manual labeling methods. Methods ML models were developed from multimodal MRI datasets of acute stroke patients within 24 h of clear symptom onset from two ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…This highlights the potential of ML algorithms based on DWI and FLAIR features to identify the onset time of stroke and guide decision on thrombolysis. Liang et al ( 33 ) developed ML models based on diffusion- and perfusion-weighted imaging fusion (DP fusion) to identify stroke within 4.5 h. The results revealed that DP fusion-based ML models yielded a greater net benefit than DWI- and PWI-based ML models, suggesting that in addition to selecting more advanced algorithms, integrating different imaging data could be enhance model performance.…”
Section: Application Of Ai In Ischemic Strokementioning
confidence: 99%
“…This highlights the potential of ML algorithms based on DWI and FLAIR features to identify the onset time of stroke and guide decision on thrombolysis. Liang et al ( 33 ) developed ML models based on diffusion- and perfusion-weighted imaging fusion (DP fusion) to identify stroke within 4.5 h. The results revealed that DP fusion-based ML models yielded a greater net benefit than DWI- and PWI-based ML models, suggesting that in addition to selecting more advanced algorithms, integrating different imaging data could be enhance model performance.…”
Section: Application Of Ai In Ischemic Strokementioning
confidence: 99%